2020
DOI: 10.1038/s41598-020-60375-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Target Enrichment Platforms for Circulating Tumor DNA Detection

Abstract: chow 1* cancer-related mortality of solid tumors remains the major cause of death worldwide. circulating tumor DNA (ctDNA) released from cancer cells harbors specific somatic mutations. Sequencing ctDNA opens opportunities to non-invasive population screening and lays foundations for personalized therapy. in this study, two commercially available platforms, Roche's Avenio ctDNA Expanded panel and QIAgen's QIAseq Human Comprehensive Cancer panel were compared for (1) panel coverage of clinically relevant varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 42 publications
(31 reference statements)
1
14
0
Order By: Relevance
“…Here we describe the results from a commercially available pancancer mutation panel evaluated with respect to both tumor and white cell cfDNA in a large, prospectively collected and annotated sample cohort from resected EAC. [11][12][13][14][15][16]…”
Section: Introductionmentioning
confidence: 99%
“…Here we describe the results from a commercially available pancancer mutation panel evaluated with respect to both tumor and white cell cfDNA in a large, prospectively collected and annotated sample cohort from resected EAC. [11][12][13][14][15][16]…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most prevalent way to analyze ctDNA employs next-generation sequencing (NGS) in combination with multiplex PCR to check a panel of hotspot mutations, which can be either generic to all tumors or specific to a certain cancer type [ 13 , 14 ]. Although low cost and easy to design, ctDNA panels generated these ways can potentially miss important mutational clones in some patients if the mutations are not included in the panel targets, therefore result in inaccurate evaluation of disease status and treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…However, TSO500 panel required higher number of sequencing reads due to its larger panel size (500 genes) and required higher cfDNA input (30 ng) making it less economical and clinically feasible in comparison to Avenio assay. A similar study was recently reported by Lam, et al in which the AVENIO platform was compared to Qiagen's QIAseq Human Comprehensive Cancer panel for panel coverage of clinically relevant variants and overall sequencing performance [21]. Detailed results from both comparison studies reveal strengths and shortcomings unique to each of these different assays.…”
Section: Discussionmentioning
confidence: 71%